Răspunsuri

2014-07-27T19:29:36+03:00
1)
E(a) = √(a-3)² + l a - 1 l + 2l -a l
E(1) = √(1-3)² + l 1 - 1 l + 2l -1 l = 2 + 0 + 2 = 4

2)
E(x) = x² - 5x + 6 + (x + 2)(x - 3)
E(2) = 2² - 5*2 + 6 + (2 + 2)(2 - 3) = 4 - 10 + 6 + (4)*(-1) =  4 -10 + 6 - 4 = -6 + 6 - 4 = -4


La Ex. 2, corect este: E(2) = 2² - 5*2 + 6 + (2 + 2)(2 - 3) = 4 - 10 + 6 - 4 = -4. Am omis un "6" la rezolvare si nu mai pot intra in editare.
bine mersi
N-ai pentru ce...
Am corectat.
bine mersi
Cel mai inteligent răspuns!
2014-07-27T19:36:05+03:00
1) E(1)= √ (1-3)² + |1-1| +2|-1|=

=|1-3| +|0|+ 2*1=

=  |-2| +2= 2+2=4

2)E(2)= 2² -5*2 +6 +(2+2)(2-3)=

= 4 -10 +6 + 4 *(-1)=

= -6 +6 -4=  -4